Prostate-specific membrane antigen-based imaging for stereotactic irradiation of low-volume progressive prostate cancer: a single-center experience - Varga, Linda; Besenyi, Zsuzsanna; Paczona, Viktor R.; Farkas, István; Urbán, Szabolcs; Sipka, Gábor; Pávics, László; Varga, Zoltan; Fodor, Emese; Hideghéty, Katalin; Olah, Judit; Bajory, Zoltán; et al. (Frontiers in Oncology, 2023)
Introduction Prostate-specific membrane antigen (PSMA) is a transmembrane protein that may be expressed on the surface of prostate cancer (PC) cells. It enables a more sensitive and specific diagnosis PC, compared to conventional anatomical imaging. Aim The integration of PSMA-based imaging in the personalized radiotherapy of PC patients and the evaluation of its impact on target volume definition if stereotactic body radiotherapy (SBRT) is planned for locally recurrent or oligometastatic disease. Patients and methods The data from 363 examinations were analyzed retrospectively. Inclusion criteria were histologically verified PC and clinical data suggesting local recurrence or distant metastasis. Whole-body 99mTc-PSMA-I&S single-photon emission computed tomography (SPECT)/CT or 18F-JK-PSMA-7 positron emission tomography/computer tomography (PET/CT) was carried out, and the evaluation of the scans and biological tumor volume contouring was performed at the Department of Nuclear Medicine. The target volume delineation on topometric CT (TCT) scan was performed at the Department of Oncotherapy. The comparison of the two volumes was performed by image fusion and registration. Results From 363 PSMA isotope-based examinations, 84 lesions of 64 patients were treated with SBRT. In 50 patients, 70 lesions were examined for intermodality comparison. The target volume defined by the PSMA density was significantly smaller than the tumor size defined by the TCT scan: GTVCT (gross tumor volume on the TCT), 27.58 ± 46.07 cm3; BTVPSMA (biological target volume on the PSMA-based examination), 16.14 ± 29.87 cm3. During geometrical analyses, the Dice similarity coefficient (DSC) was 0.56 ± 0.20 (0.07–0.85). Prostate-specific antigen (PSA) control was performed to evaluate the response: mean pre-radiotherapy (pre-RT) PSA was 16.98 ng/ml ( ± SD: 33.81), and post-RT PSA at 3 months after SBRT was 11.19 ng/ml ( ± SD: 32.85). Three-month post-therapy PSMA-based imaging was performed in 14 cases, in which we observed a decrease or cessation of isotope uptake. Conventional imaging control was performed in 42 cases (65.6% of all cases): 22 (52.4%) complete remissions, 14 (33.3%) partial remissions, four (9.5%) stable diseases, and two (4.8%) progressive diseases were described. Conclusion PSMA-based imaging is a promising diagnostic method for specifying the stage and detecting the low-volume progression. Our results suggest that PSMA-based hybrid imaging can influence treatment decisions and target volume delineation for SBRT.